Local Government Autonomy in Nigeria Problems and Prospects: A Case Study Of Ngor-Okpala Local Government Area, Imo State - Okere, Nnanna Victor (My University, 2015)
In the present day globalized world modern States have recognized the necessity to have in place a system of government at the local level. This acceptance can consequently be said to be worldwide; in as much as the practice and organization differ from one state to the other. These variances are most time and again a reflection of the socio cultural cum political history and particularities of individual states. Even though the systems in practice in various countries may have a lot of divergences, one distinctive feature that makes a lot of difference, is the level of autonomy. Consequently the question of whether this local government is accepted as a distinct tier of government or an appendage of either the federal or regional government is very essential. However, in any scenario the most vital thing is the effectiveness of the local government. Remarkably, it depicts the level of involvement of the people at the grassroots. If it is a distinct level of government for example, it shows that the local persons would take part in governance, since the main players would have to come from amongst them whether democratically elected or selected. But If it is an extension of Central or State government, the local populace would not participate actively in the conduct of the affairs of the local government as that Federal or State would be in charge for its employment and policies. At this juncture it is as absolutely necessary to pinpoint out that in as much as there are distinctions among Nation-States, so also are there diversities within these Nation-States at various time periods. Therefore any meaningful study of local government systems should take the issue of autonomy very seriously. The bottom-line is to identify the circumstances and dynamics that shape the colorations of the system at any given situation. However, a survey was conducted at Ngor\Okpala Local Government of Imo State Nigeria where 93 self-identifying individuals answered a questionnaire. They were asked to respond on issues concerning Local government autonomy in general. The main finding of this research is that autonomy is the key to grassroots participation at local government administration in Nigeria. This is further supported by the fact that the various reforms by Nigerian government in the past on how to involve active participation of grassroots populace in governance have not translated into growth and development and did not yield the desired result. It is adjudged that total autonomy should be granted to local governments, this will go a long way in solving and avoiding conflicts between the local governments and other levels of government.
Keywords: Local Government; Autonomy; Decentralization; Devolution; Nigeria and Ngor-Okpala Local Government Area.; fi=Julkisjohtaminen|en=Public Management |; fi=Master's Degree Programme in Intercultural Studies in Communication and Administration|